Exploring Gay Men’s Use of People-Nearby Applications - Rowsell, Derek (Université d'Ottawa / University of Ottawa, 2018)
Background: Gay men have adopted the use of people-nearby applications (PNA) to connect with members of the LGBT+ community. PNA uses global positioning system (GPS) data to locate other users in the area and facilitates communication between users through online profiles and instant messaging services. Objectives: This thesis explored gay men’s process of using PNA to connect with other users. Methods: The thesis work was conducted in two phases. The first phase was a review of the existing literature with literature synthesised into major themes. The second phase was an original qualitative study that used group sessions within a qualitative descriptive method and used thematic analysis to explore experiences of PNA use. Findings: The reviewed articles (n = 40) evolved into four major themes: risk, stigma, sexuality, and community. The theme of risk was overrepresented in the literature and comprised research that reviewed the sexual health risks of using PNA to meet partners. The review themes aligned closely with the four themes that emerged from participants’ (n = 6) experiences that were revealed in the original qualitative study: community, hope, stigma, and doubt. The themes of hope and doubt were found to be driving forces in a cyclical pattern of use reported by the participants, wherein users will repeatedly experience cycling phases of app use and disuse. Conclusion: Phase one of this thesis work exposed a gap in the knowledge related to the process of gay men using PNA. Phase two began to fill that gap by exploring the process of using PNA and furthering academic knowledge of how gay men interact and experience PNA use. The knowledge created in this thesis may assist nurses by providing them with improved cultural understanding of gay men and facilitate open communication between nurses and gay clients.
Keywords: LGBT; Grindr; People-nearby Applications